Mating Design and Genetic Structure of a Multi-Parent Advanced Generation Intercross (MAGIC) Population of Sorghum (Sorghum bicolor (L.) Moench) - Ongom, Patrick O. (G3 (Bethesda), 2017)
Multi-parent advanced generation intercross (MAGIC) populations are powerful next-generation mapping resources. We describe here the mating design and structure of the first MAGIC population in sorghum, and test its utility for mapping. The population was developed by intercrossing 19 diverse founder lines through a series of paired crosses with a genetic male sterile (MS) source, followed by 10 generations of random mating. At the final stage of random mating, 1000 random fertile plants in the population were identified and subjected to six generations of selfing to produce 1000 immortal MAGIC inbred lines. The development of this sorghum MAGIC population took over 15 yr. Genotyping-by-sequencing (GBS) of a subset of 200 MAGIC lines identified 79,728 SNPs, spanning high gene-rich regions. Proportion of SNPs per chromosome ranged from 6 to 15%. Structure analyses produced no evidence of population stratification, portraying the desirability of this population for genome-wide association studies (GWAS). The 19 founders formed three clusters, each with considerable genetic diversity. Further analysis showed that 73% of founder alleles segregated in the MAGIC population. Linkage disequilibrium (LD) patterns depicted the MAGIC population to be highly recombined, with LD decaying to r(2) [Formula: see text] 0.2 at 40 kb and down to r(2) [Formula: see text] 0.1 at 220 kb. GWAS detected two known plant height genes, DWARF1 (chromosome 9) and DWARF3 (chromosome 7), and a potentially new plant height quantitative trait locus (QTL) (QTL-6) on chromosome 6. The MAGIC population was found to be rich in allelic content with high fragmentation of its genome, making it fit for both gene mapping and effective marker-assisted breeding.